تحليل صنع القرار من منظور العقائد السياسية - زنودة, منى (revue mofakir, 2018)
‫‫‪The‬‬ ‫‪political‬‬ ‫‪belief‬‬ ‫‪system‬‬ ‫‪of‬‬ ‫‪the‬‬ ‫‪leaders‬‬ ‫‪has‬‬ ‫‪an‬‬ ‫‪important‬‬ ‫‪role‬‬ ‫‪among‬‬ ‫‪the‬‬ ‫‪different‬‬ ‫‪factors‬‬ ‫‪which‬‬ ‫‪affect‬‬ ‫‪decision-making‬‬ ‫‪process‬‬ ‫‪in‬‬ ‫‪the‬‬ ‫‪state,‬‬ ‫‪the‬‬ ‫‪interest‬‬ ‫‪in‬‬ ‫‪this‬‬ ‫‪area‬‬ ‫‪of‬‬ ‫‪research‬‬ ‫‪has‬‬ ‫‪emerged‬‬ ‫‪through‬‬ ‫‪a‬‬ ‫‪variety‬‬ ‫‪of‬‬ ‫‪studies‬‬ ‫‪in‬‬ ‫‪the‬‬ ‫‪field‬‬ ‫‪of‬‬ ‫‪political‬‬ ‫‪psychology‬‬ ‫‪which‬‬ ‫‪are‬‬ ‫‪interested‬‬ ‫‪in‬‬ ‫‪studying‬‬ ‫‪and‬‬ ‫‪analyzing‬‬ ‫‪psychological‬‬ ‫‪aspect‬‬ ‫‪for‬‬ ‫‪the‬‬ ‫‪decision-maker‬‬ ‫‪as‬‬ ‫‪one‬‬ ‫‪of‬‬ ‫‪the‬‬ ‫‪most‬‬ ‫‪important‬‬ ‫‪dimensions‬‬ ‫‪of‬‬ ‫‪the‬‬ ‫‪decision-making‬‬ ‫‪process‬‬ ‫‪-‬‬ ‫‪as‬‬ ‫‪well‬‬ ‫‪as‬‬ ‫‪internal‬‬ ‫‪and‬‬ ‫‪international‬‬ ‫‪environments‬‬ ‫‪-‬‬ ‫‪.‬‬ ‫‪The‬‬ ‫‪belief‬‬ ‫‪system‬‬ ‫‪helps‬‬ ‫‪in‬‬ ‫‪this‬‬ ‫‪context‬‬ ‫‪the‬‬ ‫‪political‬‬ ‫‪leader‬‬ ‫‪in‬‬ ‫‪the‬‬ ‫‪simplification‬‬ ‫‪of‬‬ ‫‪reality‬‬ ‫‪according‬‬ ‫‪to‬‬ ‫‪his‬‬ ‫‪cognitive‬‬ ‫‪map‬‬ ‫‪about‬‬ ‫‪the‬‬ ‫‪world‬‬ ‫‪and‬‬ ‫‪choosing‬‬ ‫‪the‬‬ ‫‪alternative‬‬ ‫‪that‬‬ ‫‪is‬‬ ‫‪compatible‬‬ ‫‪with‬‬ ‫‪his‬‬ ‫‪political‬‬ ‫‪beliefs.‬‬ ‫‪Accordinglly‬‬ ‫‪many‬‬ ‫‪researchers‬‬ ‫‪have‬‬ ‫‪tried‬‬ ‫‪to‬‬ ‫‪develop‬‬ ‫‪a‬‬ ‫‪methodological‬‬ ‫‪tools‬‬ ‫‪in‬‬ ‫‪order‬‬ ‫‪to‬‬ ‫‪help‬‬ ‫‪shed‬‬ ‫‪light‬‬ ‫‪on‬‬ ‫‪this‬‬ ‫‪important‬‬ ‫‪dimension,‬‬ ‫‪which‬‬ ‫‪we‬‬ ‫‪will‬‬ ‫‪address‬‬ ‫‪in‬‬ ‫‪this‬‬ ‫‪study‬‬